Estimating three-dimensional nonlinear panel data models with interactive effects. Issue 10 (7th June 2017) - Ye, Xiaoqing; Wu, Xiangjun
ABSTRACT: This article considers two three-step estimation approaches to three-dimensional nonlinear panel data models with interactive effects correlated with the independent variables. We propose a Nonlinear Least Squares-Principal Component Analysis-Grid Search iterated approach to estimate the static model, and a GMM-PCA-GS iterated method to the dynamic model. Monte Carlo experiments examine the finite sample performance of the methods.